2021
DOI: 10.1039/d1se01447a
|View full text |Cite
|
Sign up to set email alerts
|

Salt screening analysis for reverse electrodialysis

Abstract: Gray: salts with OCVth < NaCl; red: salts with OCVth > NaCl and high hazard potential; yellow: salts with OCVth > NaCl, low hazard potential, expensive; green: promising salts in terms of OCVth, hazard potential and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Ionic potential (IP), a parameter for measuring the strength of ionic electric field, reflects the mobility of the oxyanion in water solution. Many studies have clearly demonstrated that the surface complexation behavior of oxyanions to contact with solid surface is highly associated with their IP. , The IP values of CH 3 COO – , HCO 3 – , MoO 4 2– , and HPO 4 2– are between those of NO 3 – and SO 4 2– (Table S6), and these oxyanions tend to connect with MnO 2 to activate Mn(VII). The enhancing performances of oxyanions for phenol removal increased linearly with their IP values (Figure e), indicating that an appropriate polarity facilitates the adsorption of oxyanions by MnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Ionic potential (IP), a parameter for measuring the strength of ionic electric field, reflects the mobility of the oxyanion in water solution. Many studies have clearly demonstrated that the surface complexation behavior of oxyanions to contact with solid surface is highly associated with their IP. , The IP values of CH 3 COO – , HCO 3 – , MoO 4 2– , and HPO 4 2– are between those of NO 3 – and SO 4 2– (Table S6), and these oxyanions tend to connect with MnO 2 to activate Mn(VII). The enhancing performances of oxyanions for phenol removal increased linearly with their IP values (Figure e), indicating that an appropriate polarity facilitates the adsorption of oxyanions by MnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] The PRO is based on water selective transport [8] whereas the RED relies on ion-selective transport. [9][10][11][12][13][14][15] A wide range of membrane materials has been demonstrated so far for SGE, including polymeric membranes, [11][12][13] solid-state metal oxides membranes, [6,7] hybrid composite membranes, [13,14,[19][20][21] and metal-organic composite membranes. [15] Recently, the low-dimensional materials such as Graphene, [14,15] and MoS 2 [16][17][18] show high energy extraction efficiencies that are several orders of magnitude higher compared to the conventional membranes because of the ion transport through these membrane scales with membrane thickness and surface charge density.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure retarded osmosis (PRO) and reverse electrodialysis (RED) are the two most focused membrane‐based technology in harnessing blue energy [3–7] . The PRO is based on water selective transport [8] whereas the RED relies on ion‐selective transport [9–15] . A wide range of membrane materials has been demonstrated so far for SGE, including polymeric membranes, [11–13] solid‐state metal oxides membranes, [6,7] hybrid composite membranes, [13,14,19–21] and metal‐organic composite membranes [15] .…”
Section: Introductionmentioning
confidence: 99%